Mexico Policy Notes - World Bank (Washington, DC, 2013)
This note presents an overview of Mexico's forthcoming reform agenda-from the World Bank's vantage point. It distills the main messages in the policy notes that make up this compendium. The purpose is not to provide definitive answers to the many policy questions likely to occupy the New Mexican administration, or to provide a comprehensive account of progress to date and policy recommendations. Instead, it is to provide a view of the main challenges facing Mexico in its quest for inclusive and sustainable growth-and to propose feasible policy options to address them. Mexico has achieved remarkable economic and social progress over the past several decades. The country has become an investment grade borrower with solid global standing in capital markets. It is a model of financial and commercial integration and of prudent macroeconomic management. The economic literature offers several explanations for Mexico's low productivity growth. An underdeveloped financial system, labor market rigidities, high informality, scarce skilled labor, regulatory barriers for doing business, and weak innovation and limited market competition are often cited as binding constraints to productivity growth. Mexico faces challenges as it seeks to develop a labor market that protects workers, creates more and better jobs for men and women, and improve their long term standard of living. Finally, a comprehensive system for tracking and monitoring progress and environmental pressures needs to be developed.